Empowerment and poverty reduction : a sourcebook - Narayan-Parker, Deepa (Washington, DC : World Bank, 2002)
Empowerment and poverty reduction, offers a framework for empowerment that focuses on increasing poor peoples freedom of choice and action to shape their own lives for empower. Based on analysis of experiences from around the world, the source book identifies four key elements to support empowerment of poor people; information, inclusion, accountability and local organizational capacity.
Includes bibliographical references.
nmn, 08/08/16
Loans
Keywords: Poverty; Community development; Empowerment; Poverty reduction